Temporal analysis of total suspended solids (TSS) at Ujung Pangkah Beach, Gresik, from 2016 - 2020 using aqua MODIS image data - Wibisana, Hendrata (Applied Engineering and Technology, 2022)
Total suspended solids (TSS) is a parameter widely used to detect pollution on the coast, especially in areas that have a sloping coastal structure where currents and waves parallel to the coast will accumulate these solids to form sedimentation gradually. This study aims to map the distribution of TSS on the coast of Ujung Pangkah Gresik where at the end of this coast there is a flow from the Bengawan Solo river. The method in this study implements remote sensing technology to collect Aqua MODIS satellite image data of from 2016 to 2020. Based on calculation results, the wavelength band 1 (660 nanometers) of the Aqua MODIS image is the best wavelength by looking at the R correlation value generated of 0.573, so it can be concluded that the Aqua MODIS satellite imagery with a resolution of 250 - 500 meters can still be used to create a mathematical model for mapping the TSS distribution on the coast. In terms of forecasting for 5 years, the reflectance value generated from the image does not give significant results, because this satellite image is very influenced by the weather, so it is very difficult to get a cloud-free image in the same month every year to extract the reflectance value.